Effects of dietary combination of chromium and biotin on egg production, serum metabolites, and egg yolk mineral and cholesterol concentrations in heat-distressed laying quails - Şahin, Kazım; Onderci, M; Şahin, Nurhan; Gursu, MF; Vijaya, J; Küçük, Ömer (Springernature, 2004)
Chromium picolinate is used in the poultry diet because of its antistress effects in addition to the fact that the requirement for it is increased during stress. This study was conducted to determine if the negative effects of high ambient temperature (34 degreesC) on egg production, egg quality, antioxidant status, and cholesterol and mineral content of egg yolk could be alleviated by combination of chromium picolinate and biotin (0.6/2.0; Diachrome(TM), as formulated by Nutrition 21 Inc.), in laying Japanese quails (Coturnix coturnix japanica). Quails (n = 240; 50 d old) were divided into 8 groups, 30 birds per group. The quails were fed either a basal diet or the basal diet supplemented with 2, 4, or 8 mg of Diachrome/kg diet. Birds were kept at 22 degreesC and 53% relative humidity (RH). At 14 wk of age, the thermoneutral (TN) group remained in the same temperature as at the beginning of experiment, whereas the heat stress (HS) group was kept in an environment-controlled room (34 degreesC and 41% RH) for 3 wk. Heat exposure decreased performance when the basal diet was fed (p = 0.001). Diachrome supplementation at 4 and 8 mg/kg diet, increased feed intake (p = 0.05), egg production (p = 0.05), feed efficiency (p = 0.01), egg weight (p = 0.05), and Haugh unit (p = 0.01) in quails reared under heat stress conditions. Heat exposure increased concentrations of serum malondialdehyde (MDA) (p = 0.001), glucose, and cholesterol (p = 0.01), which were elevated by supplemental Diachrome (p less than or equal to 0.05). Egg yolk Cr, Zn, and Fe (p = 0.01) concentrations increased linearly, whereas MDA and cholesterol concentrations decreased (p = 0.05) as dietary Diachrome supplementation increased in HS groups. Similar effects of supplementation on serum levels of glucose and cholesterol (p = 0.05) and egg yolk concentrations of cholesterol (p = 0.05) and Cr (p = 0.01) were observed in TN groups. No significant differences in other values were observed in the TN groups. Results of the present study suggest that supplementation with Diachrome protects the quail by reducing the negative effects of heat stress.
Keywords: chromium; biotin; heat stress; egg; cholesterol; MDA; quails